Comparative Study of Multistorey RC Building Using Static and Dynamic Analysis Using NBC 105: 2020 (International Journal of Innovative Research in Engineering & Management, 2022)
Recent high-intensity earthquakes have  gained increasing media attention in a number of countries,  including Nepal. Buildings' structural insufficiency to  handle seismic loads has been brought to light by the  ensuing losses, mainly human life, caused by earthquakes.  Post-earthquake studies have shown that masonry  structures, in comparison to other building types, are the  most earthquake-prone and have incurred the greatest  damage during prior quakes . Even if many new building  methods have been developed in the modern period,  masonry still has a significant place in the construction  business. As Nepal is highly under the sesmic forces no any  codal provision is there before the 1992 A.D Earthquake.  With the importance, Nepal introduced the code on 1994  A.D which on dealed mostly with the Sesmic Behaviour.  After the Massive Earthquake on 2015A.D, there was the  challenge on Upgrading the Codal Provision on NBC,  which incorporated both the sesmic and dynamic forces,  which results on NBC 105:2020. The primary purpose of  the research is to examine multi-story reinforced concrete  building models using static and dynamic analysis of the  same design utilising the latest version of Nepal's building  code (NBC:105:2020). The Comparative study of the Static  and Dynamic forces on G+9 Multistory RC Building is  considered of the analysis.
Keywords: Base Shear; Storey Shear; Seismic Analysis; Storey Drift